2011
DOI: 10.1111/j.1365-2869.2011.00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum proteomic changes in adults with obstructive sleep apnoea

Abstract: SUMMARYTo examine whether differentially expressed proteins are present in the serum of patients with obstructive sleep apnoea (OSA), iTRAQ techniques (isobaric tags for relative and absolute quantification) were employed in a prospective study. Individuals were assigned to either a non-OSA control group (apnoea-hypopnoea index, AHI <5) or an OSA group (AHI ‡5). Blood samples were collected, aliquoted and frozen at )80°C. Protein digestion and tagging with iTRAQ4plex â and mass spectrometry analysis was then p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Serum proteomics has been conducted on only a limited basis, revealing potential increases in a number of known proteins, such as fibronectin and ApoB100 in OSA patients [45]. Another study utilizing 2D electrophoresis noted increased serum levels of haptoglobins and reduced levels of paraoxonase-1 in OSA patients [46].…”
Section: Discussionmentioning
confidence: 99%
“…Serum proteomics has been conducted on only a limited basis, revealing potential increases in a number of known proteins, such as fibronectin and ApoB100 in OSA patients [45]. Another study utilizing 2D electrophoresis noted increased serum levels of haptoglobins and reduced levels of paraoxonase-1 in OSA patients [46].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent study revealed differential serum protein expression in adults with OSA. These proteins were primarily those involved in lipid and vascular metabolic pathways, and the changes varied according to disease severity 90. It is unclear how this line of investigation will evolve and whether exploration of the deep proteome in plasma samples will enable development of a cluster biomarker panel that offers robust and accurate diagnostic capabilities.…”
Section: Proteomicsmentioning
confidence: 99%
“…Thus, it has become a powerful analytical technique for discovering disease biomarkers and drug targets. This strategy has recently been employed successfully to identify new markers for certain diseases, such as adult obstructive sleep apnea [12], autoimmune diseases [13,14], head-and-neck cancer [15], lung Cancer [16], and hepatocellular carcinoma [17].…”
Section: Introductionmentioning
confidence: 99%